Silicon carbide-supported iron nanoparticles encapsulated in nitrogen-doped carbon for oxygen reduction reaction. Issue 9 (11th December 2015) - Li, Jiayuan; Wang, Jing; Gao, Dunfeng; Li, Xingyun; Miao, Shu; Wang, Guoxiong; Bao, Xinhe
Abstract : Iron nanoparticles encapsulated in nitrogen-doped carbon (Fe@N–C) supported on a SiC core with a derived nitrogen-doped carbon shell (SiC@N–C) show much higher activity for oxygen reduction reaction than SiC, SiC@N–C and SiC-supported Fe3 Si in alkaline medium. Abstract : Silicon carbide (SiC) was extracted using CCl4 and NH3 at 800 °C to form a SiC core with a derived nitrogen-doped carbon shell (SiC@N–C), which is explored as a supporting material for iron nanoparticles encapsulated in nitrogen-doped carbon (Fe@N–C) due to its excellent corrosion resistance. The carbon shell around SiC is essential to successfully grow Fe@N–C around SiC@N–C during pyrolysis of cyanamide and iron acetate. In sharp contrast, Fe3 Si supported on SiC was obtained using pristine SiC as the supporting material. Fe@N–C/SiC@N–C showed much higher activity for oxygen reduction reaction than SiC@N–C and Fe3 Si/SiC, even exceeding that of a commercial Pt/C catalyst in alkaline medium. Furthermore, Fe@N–C/SiC@N–C also demonstrated higher durability and methanol resistance than the Pt/C catalyst.